Evaluation and review of educational programs and delivery of care services for the elderly, Western General Hospital, Edinburgh, UK: A practical module for developing countries - Zeinalzadeh, Alihossein (Social Determinants of Health, 2019)
The developing world is going grey. These countries need to establish new care services according to the standards of Healthcare Improvement. The present report emphasizes on important management components of the elderly care which can facilitate the initiating and continuing the good practice in context of multidisciplinary team. The principle focus of this assessment is on the team activities. Some of the important features of this team approach include increase in quality of services provided, mutual respect, empathy, increased sense of responsibility, and accurate follow-ups. The aim of the present report was evaluation and review of educational programs, delivery of care services for elderly patients admitted to Western General Hospital to provide a module for developing countries.